2004
DOI: 10.1143/jjap.43.4619
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Behavior of Terphenyl Self-Assembled Monolayer Studied by a Pin-on-Plate Method and Friction Force Microscopy

Abstract: We investigated the friction properties of organic self-assembled monolayers (SAMs) using a pin-on-plate method, friction force microscopy (FFM) and X-ray photoelectron spectroscopy (XPS). A pin-on-plate tribometer was used for friction measurements under practical conditions. The sliding speed and load in the pin-on-plate method were higher than those of conventional FFM. Although the friction coefficients of terphenyl methane thiol SAMs measured by FFM were higher than those of soft octadecanethiol (ODT) SAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…This is important in that tribological stress could be applied exclusively onto the SAM films, i.e., without penetrating to the underlying substrate, and thus their tribological properties as boundary-lubricant films can be probed. In contrast, tribological contacts involving SAM films probed by more conventional, macroscale approaches, such as pin-on-disk tribometry [19][20][21][22][23][24], have generally resulted in irreversible damage to the samples, both the SAM films and the supporting substrates, which renders the interpretation of the observed tribological properties far more complicated.…”
Section: Introductionmentioning
confidence: 99%
“…This is important in that tribological stress could be applied exclusively onto the SAM films, i.e., without penetrating to the underlying substrate, and thus their tribological properties as boundary-lubricant films can be probed. In contrast, tribological contacts involving SAM films probed by more conventional, macroscale approaches, such as pin-on-disk tribometry [19][20][21][22][23][24], have generally resulted in irreversible damage to the samples, both the SAM films and the supporting substrates, which renders the interpretation of the observed tribological properties far more complicated.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 6 shows that the effects of molecules appeared only in the low normal load region. In our previous study [14], we analyzed normal octadecanethiol SAM surfaces after friction tests by XPS. In that study, 95% of the molecules remained on surface after a sliding distance of 180 m under a load of 30 mN.…”
Section: The Effects Of Molecules Upon the Friction Propertiesmentioning
confidence: 99%
“…Another reason is that the SAM formation process on Au substrates is easier than that on other substrates such as silicon made from organosilianol compounds. For example, the authors have investigated the tribological behavior of organosulfur molecule SAMs on Au using a pin-on-plate method [13][14][15]. In our previous study, we found that the friction coefficients were dependent on the alkyl chain length and that even a monolayer film was sufficiently durable against friction, although the friction coefficients were slightly high at 0.2 to 0.4.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations